2018
DOI: 10.1021/acssuschemeng.8b03622
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Techno-economic, Uncertainty and Life Cycle Analysis of Lignocellulosic Biomass Solvent Liquefaction and Sugar Fermentation to Ethanol

Abstract: This study compares the use of three low boiling point polar aprotic solvents, tetrahydrofuran (THF), acetone, and 1,4-dioxane, for extracting biomass sugars in ethanol biorefineries. The techno-economic analysis employs experimental data to build a chemical process model and estimate capital and operating costs of a commercial-scale biorefinery. The biomass solvent liquefaction in a 2000 metric tonne per day sugar fermentation biorefinery yields ethanol at minimum fuel-selling prices (MFSP) of $2.98 to $4.06 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 35 publications
2
31
0
Order By: Relevance
“…[ 32 ] glucose/hemicellulose/lignin, bioethanol/lignin/furfural organosolv beech woodchips 1 t h −1 hardwood chips Li et al . [ 33 ] bioethanol dilute sulfuric and organic acid forest residues 1 MJ ethanol Moncada et al . [ 34 ] glucose production organosolv spruce woodchips 1 kg of dry glucose ✓ mass/energy flows Bright & Strømman [ 35 ] bioethanol dilute sulfuric acid poplar chips 1000 km distance Mu et al .…”
Section: An Overview Of Life Cycle Assessment Studies Of Woody Biomass Conversion To Bio-chemicalsmentioning
confidence: 99%
“…[ 32 ] glucose/hemicellulose/lignin, bioethanol/lignin/furfural organosolv beech woodchips 1 t h −1 hardwood chips Li et al . [ 33 ] bioethanol dilute sulfuric and organic acid forest residues 1 MJ ethanol Moncada et al . [ 34 ] glucose production organosolv spruce woodchips 1 kg of dry glucose ✓ mass/energy flows Bright & Strømman [ 35 ] bioethanol dilute sulfuric acid poplar chips 1000 km distance Mu et al .…”
Section: An Overview Of Life Cycle Assessment Studies Of Woody Biomass Conversion To Bio-chemicalsmentioning
confidence: 99%
“…Levoglucosenone (LGO), an anhydro-sugar with a double bond combined with a ketone and aldehyde, in addition to two hydroxyl groups (Tang et al, 2017b;Krishna et al, 2018), has shown a huge potential to serve as a bio-based platform chemical (Nguyen et al, 2015;He et al, 2017a;Li et al, 2018). Cao et al (2015) found that the highest yields of LGO could be obtained in both THF and GVL aqueous co-solvents.…”
Section: Levoglucosan and Fermentable Sugarmentioning
confidence: 99%
“…Liquefaction in the presence of solvent has been considered as an efficient approach for the production of valuable chemicals or biofuels from lignocellulose, since solvents significantly improve the mass and heat transfer of solid lignocellulosic biomass (Li et al, 2018). Compared to pyrolysis, solvent liquefaction requires relatively moderate reaction temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The methanol recovery rate is assumed to be 99%. 36 We estimate the methanol recovery cost to be $7 per MT of methanol based on work by Shahandeh et al 37 This cost includes the annualized capital and operating costs of the distillation process.…”
Section: Techno-economic Analysismentioning
confidence: 99%